Exploring the relationship between customer loyalty and financial performance of banks: Customer open innovation perspective - Md. Harun Ur Rashid; Mohammad Nurunnabi; Mahfuzur Rahman; Md. Abdul Kaium Masud (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In the age of technology, continuous innovation is the ultimate motto of the financial sector to attract customers. Firms in the financial sector must be innovative in terms of service quality and operational performance to obtain customer loyalty and gain financial stability. A dearth of studies on customer loyalty and financial performance of Islamic Banks motivated the authors to examine the relationship between customer loyalty and financial performance. The study also explores whether the service qualities have any impact on customer loyalty. The study uses both primary and secondary data to conclude the research objectives. A survey of 356 questionnaires was carried out among the customers of the selected Islamic banks of Bangladesh to gather information regarding customer service quality and customer loyalty, while financial performance data were attained from the annual reports. Moreover, the study follows the SERVQUAL model's five dimensions (tangibles, empathy, assurance, reliability, and responsiveness) to determine the service quality of Bangladeshi Islamic Banks. Rigorous statistical techniques, including exploratory factor analysis, reliability testing, and regression analysis were used to investigate the hypothesis. The study empirically documents a positively significant impact of service quality (tangibles, empathy, reliability, and responsiveness) on customer loyalty, while assurance shows an insignificant relationship. Furthermore, the study does not find any significant relationship between customer loyalty and the financial performance of Bangladeshi Islamic Banks. The findings of the study profoundly denote that the financial performance of Bangladeshi Islamic Banks mostly depends on many other financial and non-financial factors, rather than customer loyalty.
Keywords: 650; service quality; customer loyalty; financial performance; Islamic banks; SERVQUAL; Bangladesh